The role of family-centered care in enhancing stroke rehabilitation outcomes: an integrative literature review - Mendrofa, Fery Agusman Motuho; Iswanti, Dwi Indah; Saifudin, I Made Moh. Yanuar (International Journal of Public Health Science (IJPHS), 2025)
Family-centered care (FCC), which emphasizes the involvement of family members as active participants in the care process, represents a significant paradigm within the realm of stroke rehabilitation. This study aimed to locate and synthesize the most recent evidence concerning the advantages, methodologies, and obstacles associated with the integration of FCC in stroke rehabilitation. The approach taken involves conducting an integrative literature review following the guidelines set forth by Whittemore and Knafl. A thorough exploration of four databases including PubMed, CINAHL, Scopus, and PsycINFO, was carried out, focusing on both quantitative and qualitative studies published between January 2012 and December 2022. Inclusion criteria comprised studies involving adult stroke patients undergoing rehabilitation, detailing family-centered interventions, and presenting outcomes for either the patients or their families. Upon the screening process, 25 studies met the inclusion criteria and were included in the analysis. Various strategies have been identified to effectively involve families in the rehabilitation process, such as educational initiatives, collaborative planning for home-based care, and provision of support for caregivers. However, the implementation of FCC faces challenges stemming from factors at the system level, provider level, and patient/family level, in conclusion, the integration of FCC in stroke rehabilitation yields substantial benefits for both patients and caregivers. It is imperative for nurses to engage families as collaborative partners, tailor interventions according to specific requirements, offer assistance to caregivers, and instigate changes at the systemic level.